Conspicuous consumption, luxury products and counterfeit market in the UK - Pham, Trang Huyen My; Nasir, Muhammad Ali (The European Journal of Applied Economics, 2016)
The fast growth of fashion brands and the popularity of counterfeit goods has posed certain challenges to the existing and new luxury fashion brand players. This study elaborates on the factors driving the market for counterfeit products in the UK. The data collected by means of survey questionnaires from 306 respondents and empirical techniques including descriptive and inferential statistics (correlation and multiple regression analysis), have shown that the consumers have a negative attitude towards counterfeit luxury products. However, they showed fewer tendencies to seek for a brand whose counterfeit cannot easily be found and preferred to buy a genuine rather than a counterfeit. In terms of frequency of purchase, reversion to counterfeit has negative impact, unlike the tendency to seek a brand whose counterfeit is hard to find. The overall results show that the attitude and acceptance of counterfeit do not greatly prevail in the market. However, about 27% of respondents demonstrated either a positive or a neutral tendency towards counterfeit products, which could have serious implications for the luxury goods market.